PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN MEKANISME COORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA) - SRI INDESWARI (Jurnal Ekonomi, 2015)
This study was conducted to see the effect of firm size and leverage to earningsmanagement with corporate governance mechanisms as a moderating variable.The object under study is a banking company that is listed on the Indonesia StockExchange. This chapter will discuss the results of testing structural equationmodels or based on statistical analysis performed by multiple linear regressionthrough t-test statistical coefficient of determination and assessment. Before thetest, the first test will be performed classical assumption of data normality test,multicolinearity test, heteroscedasticity test and autocorrelation test.These results indicate that 1) the independent commissioner has no effect on therelationship between firm size and earnings management 2) an independentCommissioner effect on the relationship between leverage and earningsmanagement 3) institutional ownership has no effect on the relationship betweenfirm size and earnings management 4) Ownership of institutional influence therelationship between leverage and earnings management 5) The audit committeehas no effect on the relationship between firm size and earnings management 6)the audit committee did not affect the relationship between leverage and earningsmanagement.